Effect of climatic factors, plant varieties, and planting densities on arthropod dynamics in rice crops in Yopal-Casanare, Colombia - Obregon, Diana; Hernández Guzmán, Francisco Javier; Ríos Moyano , Diana Katherinne (Revista Colombiana de Entomología, 2021)
The diversity and population dynamics of the arthropods present in rice crops under dry and irrigated planting systems were evaluated, with two rice varieties (Fedearroz 174 and Fedearroz 733), and in three planting densities (60, 100, and 180 kg/ha) in relation to different climatic variables. For specimen collection, 10 double entomological net passes were performed every eight days from emergence to the start of the maturation phase. The morphotypes found were identified and grouped according to their type of interaction with the crop in sap-suckers, chewers, predators, and parasitoids. The most relevant climatic variables were selected with a Random Forest analysis. 126 morphotypes were identified in 12 orders. The greatest richness was found in Hemiptera, Coleoptera and Diptera, as well as in the group of suckers. No differences were found in the abundance or richness of arthropods between varieties or planting densities. The irrigation system presented a greater total abundance of arthropods compared to the rainfed system, but in this system, there was higher species richness. Parasitoid and predator populations were negatively correlated with chewers but there was no effect on sap-suckers. Temperature and relative humidity were the most relevant climatic variables in arthropod dynamics. These results contribute to develop pest monitoring and management systems that take into account the dynamics of interaction between ecological groups and the effect of local climate.